2011
DOI: 10.1007/s10562-011-0680-5
|View full text |Cite
|
Sign up to set email alerts
|

Acid Strength of Pt-Zeolite Catalysts: Evidence of Metal-Support Interaction from Linear Free-Energy Relationship

Abstract: The acid strength of Pt-HBeta and Pt-HMordenite zeolite catalysts were estimated by H/D exchange of substituted benzenes with the use of linear free-energy relationship, through the use of the Hammet-Brown equation. The results indicated that compared with the parent acidic zeolite, the incorporation of Pt metal leads to a significant decrease in the acid strength, estimated by the slope (q) of the logarithm of the relative rate (k X /k H ) with the r ? constant of the substituent, indicating a lower degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Furthermore, this decrease of the strength of the Brønsted acid sites was found to be more pronounced for Ir‐modified zeolites Y and Beta than for the Pt‐modified materials. The observed decrease of acid strength upon Pt modification agrees well with the results of Tourinho et al 12. who investigated H/D exchange rates of substituted benzenes and the thermodesorption of n ‐butylamine on zeolites Pt/Beta and Pt/mordenite.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, this decrease of the strength of the Brønsted acid sites was found to be more pronounced for Ir‐modified zeolites Y and Beta than for the Pt‐modified materials. The observed decrease of acid strength upon Pt modification agrees well with the results of Tourinho et al 12. who investigated H/D exchange rates of substituted benzenes and the thermodesorption of n ‐butylamine on zeolites Pt/Beta and Pt/mordenite.…”
Section: Resultssupporting
confidence: 90%
“…and Kubička et al 10. The formation of specific metal‐proton adducts with a lower acid strength, as suggested by Tourinho et al.,12 however, would lead to new 1 H MAS NMR signals in the spectra of noble‐metal‐modified zeolites, which were not observed in this study.…”
Section: Resultsmentioning
confidence: 41%
See 1 more Smart Citation
“…On the other hand, heteropoly acids can provide the desired acidity but are subject to quick deactivation by solvation and are of poor thermal stability. The various inconsistencies with these materials therefore attributed a shift by the refineries to zeolite-based catalysts [103], [107] and [108]. Reactions over zeolites are strongly dependent on structure-acidity properties and these are in turn critical for the hydroisomerization process.…”
Section: Please Put Scheme 3 Herementioning
confidence: 99%
“…A recent study on the free energy relationship with acidic strength of solid acid catalysts showed that the acid strength varied in the order Amberlyst‐15>zeolite Beta>niobic acid>K‐10 Montmorillonite, whereas n ‐butylamine thermodesorption showed strong/weak acidity ratios in the order of zeolite Beta>K‐10 Montmorillonite>niobic acid 18. 19 Amberlyst‐15 could not be measured by this method due to its low thermal stability. Niobium phosphate is expected to have a higher acid strength than that of niobic acid from NH 3 adsorption studies;20 however, this technique measures both Lewis and Brønsted acid sites, which may not both be catalytically active 16.…”
Section: Discussionmentioning
confidence: 99%